Engineered colloidosomes as biomimetic cellular models. (March 2023) - Wei, Minghao; Lin, Yiyang; Qiao, Yan
Abstract: Synthetic counterparts of living cells (protocells) bridge the gap between the non-living and living world. Cell-sized colloidosomes have been explored as biomimetic cell models due to their wide-ranging building blocks, structural robustness, and facile functionalization. Here we review the recent progresses in the design of cell-like colloidosomes as protocell models to imitate the advanced cellular behaviors. We summarize the methods to develop hierarchical compartments by organizing a range of building blocks (e.g., inorganic, organic and hybrid particles) via Pickering emulsion to form membranous structures that isolate themselves from the external environment. By incorporating functional units (e.g., biomolecules), these colloidosomes are capable of displaying cell-like properties such as metabolism, growth/division, motility, and communication. We envision that the hierarchical structures and versatile functions of innovative colloidosomes will further inspire the design of biomimetic soft matter that may build connections between non-living and living materials, and stimulate potential applications in the fields of soft robotics, microreactors and drug delivery. Graphical abstract: This review summarizes the rational design of colloidosomes as protocell models to mimic complex cellular behaviors, including molecular encapsulation, metabolism, growth, division, motility, chemotaxis, and communication. Image, graphical abstract